Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1365-2516.2011.02669.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the biological basis of haemophilic joint disease: experimental studies

Abstract: Haemophilia has been recognized as the most severe among the inherited disorders of blood coagulation since the beginning of the first millennium. Joint damage is the hallmark of the disease. Despite its frequency and severity, the pathobiology of blood-induced joint disease remains obscure. Although bleeding into the joint is the ultimate provocation, the stimulus within the blood inciting the process and the mechanisms by which bleeding into a joint results in synovial inflammation (synovitis) and cartilage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 109 publications
(131 reference statements)
0
67
0
4
Order By: Relevance
“…In hemophilia bleeding is very common, especially into joints, where an inflammatory, proliferative synovitis develops. This results in hemophilic arthropathy, a multifactorial event in which the deposition of iron in the joints appears to exert a central role [32]. PDT induced hemorrhagic events followed by hemosiderin formation and iron deposition in the synovial membrane may contribute to the sustained inflammation after the treatment in our CIA mice.…”
Section: Discussionmentioning
confidence: 94%
“…In hemophilia bleeding is very common, especially into joints, where an inflammatory, proliferative synovitis develops. This results in hemophilic arthropathy, a multifactorial event in which the deposition of iron in the joints appears to exert a central role [32]. PDT induced hemorrhagic events followed by hemosiderin formation and iron deposition in the synovial membrane may contribute to the sustained inflammation after the treatment in our CIA mice.…”
Section: Discussionmentioning
confidence: 94%
“…In accordance with this, local synovial iron deposits are associated with increased catabolic activities in hemophilia [4]. Careful observation of patient material supplemented with data from animal models of joint disease clearly showed that the major mechanism of hemoglobin-induced joint injury is the deposition of iron in superficial and subsynovial layers of the joint, which is a hallmark of hemophilic synovitis [5]. Iron increases proliferation of synovial cells in a concentration-dependent manner and induces upregulation of mouse double minute 2 homolog (Mdm2) gene [6].…”
Section: Introductionmentioning
confidence: 90%
“…In normal cells, the Mdm2 binds to the tumor suppressor protein p53 and prevents its function [7,8]. Therefore, Mdm2 overexpression was proposed to be a suitable target in treating the underlying cell proliferation that leads to synovitis and arthropathy in hemophilia [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Such a hypertrophic synovium is then called haemophilic synovitis. The problem is that the hypertrophic synovium is very richly vascularized, and very prone to recurrent bleeding [1,2]. We present a very uncommon cause of unresponsive elbow synovitis in an adult haemophilia patient.…”
Section: Introductionmentioning
confidence: 94%